The relationship between mobile application usages and job performance at Universiti Teknologi Mara (UiTM) Pahang, Campus Jengka / Wan Nur Shahirah Wan Rashid - Wan Rashid, Wan Nur Shahirah (Faculty of Business and Management, 2018)
This research tries to clarify the relationship between mobile application usage and job performance at Universiti Teknologi MARA (UiTM) Pahang, Campus Jengka by establishing an integrated framework for mobile application usage and job performance. The first objective of this research is to investigate the relationship between every element of mobile application usage and job performance. The second objective is to study which part in the organization that mostly requires mobile application to do a job. The process used is to collect information and data for the purpose of accomplishing a whole study. There are 83 out of 110 useable questionnaire were collected from the supporting staff at Universiti Teknologi MARA (UiTM) Pahang, Campus Jengka. The statistical tests in this research have used Reliability, Descriptive Analysis, Correlation and Regression. The results show that there is a relationship between mobile application usage and jobs' performance